African horse sickness: The potential for an outbreak in disease‐free regions and current disease control and elimination techniques. (21st July 2016) - Robin, M.; Page, P.; Archer, D.; Baylis, M.
Summary: African horse sickness (AHS) is an arboviral disease of equids transmitted by Culicoides biting midges. The virus is endemic in parts of sub‐Saharan Africa and official AHS disease‐free status can be obtained from the World Organization for Animal Health on fulfilment of a number of criteria. AHS is associated with case fatality rates of up to 95%, making an outbreak among naïve horses both a welfare and economic disaster. The worldwide distributions of similar vector‐borne diseases (particularly bluetongue disease of ruminants) are changing rapidly, probably due to a combination of globalisation and climate change. There is extensive evidence that the requisite conditions for an AHS epizootic currently exist in disease‐free countries. In particular, although the stringent regulations enforced upon competition horses make them extremely unlikely to redistribute the virus, there are great concerns over the effects of illegal equid movement. An outbreak of AHS in a disease free region would have catastrophic effects on equine welfare and industry, particularly for international events such as the Olympic Games. While many regions have contingency plans in place to manage an outbreak of AHS, further research is urgently required if the equine industry is to avoid or effectively contain an AHS epizootic in disease‐free regions. This review describes the key aspects of AHS as a global issue and discusses the evidence supporting concerns that an epizootic may occur in AHS free countries, the planned government responses, and the roles and responsibilities of equine veterinarians.